The Possession Competencies Planning of Schools Administrators of the Basic Teaching (Level two) from the view of Administrators and Teachers(Field study) - Mahmoud, Noura (Latakia University Journal - Arts and Humanities Sciences Series, 2016)
The Research aims to investigate the administrators and teachers opinion in the degree of having of Planning Competencies of Schools Administrators of the Basic Teaching (Level two), and to study the different of such opinions according to variables (the functional name, scientific and educational qualification, expertness).The sample included (262) Administrators and Teachers for the academic year 2014/2015. To achieve the objectives of the research, a questionnaire composed was designed including (70) items included competencies planning; distributed to the six areas (planning to courses, Planning to Time Management, Planning to Educational outputs, human resource management, material and finances management, Planning to Management communication of the community. The final results showed that possession the Planning Competencies were middle rated, the results did not show statistical significance differences among sample answers averages in possession the Planning Competencies according to the variables of expertness, but there are found statistically significant differences according to the variable functional name in favor of the schools administrators, also according to the variable of scientific and educational qualification in favor of the diploma educational qualification and post- graduate study. The Research suggestions to building measurement for Planning Competencies, and doing training courses before joining scholastic job.